عقود المناولة ودورها في ترقية المؤسسات الصغيرة والمتوسطة في الجزائر - حسن, قويدر; علي العربي, فرحات; عبد الفتاح, بحري (University of eloued جامعة الوادي, 2021)
تهدف الدراسة إلى ابرار دور عقود المناولة، كإحدى أهم الآلیات الداعمة لترقیة نشاط المناولة الصناعیة في المؤسسات الصغیرة والمتوسطة سعیا وراء زیادة قدراتها التنافسیة .فمن خلال تسلیط الضوء على الدور الذي انشأت من أجله إحدى هاته المراكز ممثلة في المناولة بالجزائر والمتمثل في دعم المناولة الصناعیة وإحداث تشابك بین المؤسسات من خلال الاعتماد على المؤسسات الصغیرة والمتوسطة، باعتبار أن المناولة أصبحت تعد من أهم أنواع الشراكة الاستراتيجية بین المؤسسات.The study aims to justify the role of subcontracting contracts, as one of the most important mechanisms supporting the promotion of industrial handling activity in small and medium enterprises in order to increase their competitive capabilities. By highlighting the role for which one of these centers, represented by handling in Algeria, was established, represented in supporting industrial handling and creating intertwining Between institutions by relying on small and medium enterprises, given that handling has become one of the most important types of strategic partnership between institutions.
ماستر اقتصاد
Keywords: المؤسسات الصغیرة والمتوسطة، المناولة الصناعیة، عقود المناولة; small and medium enterprises, industrial handling, handling contracts